2020
DOI: 10.3390/app10020694
|View full text |Cite
|
Sign up to set email alerts
|

Failure Trends of High-Voltage Porcelain Insulators Depending on the Constituents of the Porcelain

Abstract: The aging of porcelain insulators is responsible for the failure of power utilities. Porcelain insulators from different places in South Korea, possessing various aging times and years of installation, have been investigated to carry out lifetime statistics. These samples have a mass of 36,000 lbs and are operated at 154 kV. X-ray fluorescence (XRF) and scanning electron microscopy (SEM) were performed on the porcelain bodies of the samples collected. XRF and SEM revealed trends in the weight percentage of SiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Varieties of failure mode can be observed, such as separation of cap from body, separation of pin and shattering of porcelain body, as shown in Figure 3. The factors responsible for mechanical strength are porcelain body and the interface between cement, hardware and porcelain.The Korea Electric Power Research Institute (KEPRI) reported a reference factor known as quality factor (K), to evaluate the mechanical strength of porcelain insulators [23][24][25][26][27][28][29]. K, which evaluates porcelain insulators mechanically and electrically, was calculated by using Equation 1 for all age groups of samples, for the prevention of sudden The factors responsible for mechanical strength are porcelain body and the interface between cement, hardware and porcelain.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Varieties of failure mode can be observed, such as separation of cap from body, separation of pin and shattering of porcelain body, as shown in Figure 3. The factors responsible for mechanical strength are porcelain body and the interface between cement, hardware and porcelain.The Korea Electric Power Research Institute (KEPRI) reported a reference factor known as quality factor (K), to evaluate the mechanical strength of porcelain insulators [23][24][25][26][27][28][29]. K, which evaluates porcelain insulators mechanically and electrically, was calculated by using Equation 1 for all age groups of samples, for the prevention of sudden The factors responsible for mechanical strength are porcelain body and the interface between cement, hardware and porcelain.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…K, which evaluates porcelain insulators mechanically and electrically, was calculated by using Equation 1 for all age groups of samples, for the prevention of sudden The factors responsible for mechanical strength are porcelain body and the interface between cement, hardware and porcelain. The Korea Electric Power Research Institute (KEPRI) reported a reference factor known as quality factor (K), to evaluate the mechanical strength of porcelain insulators [23][24][25][26][27][28][29]. K, which evaluates porcelain insulators mechanically and electrically, was calculated by using Equation ( 1) for all age groups of samples, for the prevention of sudden mechanical failure of insulators.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Additionally, all the above reported approaches cannot be utilized for the active insulators onsite. The development of robust superhydrophobic surfaces for various industrial applications, including self-cleaning, anti-icing, antibacterial, oil–water separation, and corrosion resistance, has been reported several times. This study aimed to improve stress corrosion resistance by developing a superhydrophobic surface utilizing a PFPE-infused functionalized SiO 2 nanocomposite with micro–nano structures as a multifunctional treatment on porcelain insulators. …”
Section: Introductionmentioning
confidence: 99%
“…The total amount of electro-technical insulator waste grows by massive tons every year. This occurrence provokes alarming environmental contamination (Suttibak and Nitivattananon, 2008;Xie et al, 2012;Cregut et al, 2013;Sanyal et al, 2020;Pereira et al, 2022). Therefore, the disposal of electro-technical porcelain insulators has become a critical issue in many nations (Brito and Saikia, 2013;Xu et al, 2015;Khan et al, 2016;Cicek et al, 2018;Tam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%